Muscular exercise can cause highly pathological liver function tests in healthy men - Pettersson, Jonas; Hindorf, Ulf; Persson, Paula; Bengtsson, Thomas; Malmqvist, Ulf; Werkström, Viktoria; Ekelund, Mats (British journal of clinical pharmacology, 2008)
What is already known about this subject • The occurrence of idiosyncratic drug hepatotoxicity is a major problem in all phases of clinical drug development and the leading cause of postmarketing warnings and withdrawals. • Physical exercise can result in transient elevations of liver function tests. • There is no consensus in the literature on which forms of exercise may cause changes in liver function tests and to what extent. What this study adds • Weightlifting results in profound increases in liver function tests in healthy men used to moderate physical activity, not including weightlifting. • Liver function tests are significantly increased for at least 7 days after weightlifting. • It is important to impose relevant restrictions on heavy muscular exercise prior to and during clinical studies. Aim To investigate the effect of intensive muscular exercise (weightlifting) on clinical chemistry parameters reflecting liver function in healthy men. Methods Fifteen healthy men, used to moderate physical activity not including weightlifting, performed an 1 h long weightlifting programme. Blood was sampled for clinical chemistry parameters [aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LD), gamma‐glutamyl transferase (γGT), alkaline phosphatase (ALP), bilirubin, creatine kinase (CK) and myoglobin] at repeated intervals during 7 days postexercise and at a follow‐up examination 10–12 days postexercise. Results Five out of eight studied clinical chemistry parameters (AST, ALT, LD, CK and myoglobin) increased significantly after exercise (P < 0.01) and remained increased for at least 7 days postexercise. Bilirubin, γGT and ALP remained within the normal range. Conclusion The liver function parameters, AST and ALT, were significantly increased for at least 7 days after the exercise. In addition, LD and, in particular, CK and myoglobin showed highly elevated levels. These findings highlight the importance of imposing restrictions on weightlifting prior to and during clinical studies. Intensive muscular exercise, e.g. weightlifting, should also be considered as a cause of asymptomatic elevations of liver function tests in daily clinical practice.